1881 N.C. Sess. Laws 731, ch. 40, § 43 - (:unkn) unknown (General Publisher, 1881)
the Board of Aldermen]1 shall have power to make ordinances to prohibit or control the firing of fire-arms, fire crackers, torpedoes and other explosive material, and to govern the sale thereof in the city
--
Keywords: DISCHARGE; TRANSFER